DETEKSI DAN PEMODELAN GERAKAN OBYEK BERGERAK MENGGUNAKAN TEKNIK VIDEOGRAFI - , SRI WINDARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Videography technique is one branch of close range photogrammetry technique that records the object frame by frame in video format. Object that can be recorded can be static object or moving object. This research used videography technique to record the movement of an object by using multiple video cameras (handycam). The results of acquisition data from recording object was used to detect movement of object and make a 3D animation model, so that moving object motion was looked more visible and informative. This research used some stages namely preparation, acquisition data, processing data and analysis of the results. The preparation stage included preparation for site and research object, camera calibration, installation premark in area observation and object research. Data acquisition stage was done by recording the object. Processing data stage consisted of converting data to video format, selecting and cutting frame video, processing data image using software Photomodeller Scanner 2013, modeling ball using Autodesk 3ds Max Design 2013, and modeling of movement of the ball. Analysis of the results in this research included accuracy coordinates image processing, precision of ball position, and the movement of the ball. The results in this research indicated that the level of accuracy of coordinates image still had low accuracy as indicated by standard deviation of X component about ± 0.070 m, Y component about ± 0.056 m and Z component about ± 0.006 m. Moreover precision of the ball position of image still had low precision with the RMS residual value between 0.057 pixels to 4.299 pixels. By modeling the movement of the ball, it can produce graph results of movement of the ball that shows straight line sloping upward toward the X-axis, the line up and down on the Y axis, and the parabolic line up and down with 4 peaks on the Z axis. Keywords : modeling, motion detection, videography